(3GdQbGHI GdbVGFjI Ydi GdJMcje hab CMcGe fXGe GdJMcje GdSYhOj (B/s - (3eMeO Hf MSf Hf eMeO GdYSjQjs; (3SejMI eUWai GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2010)
(3JfGhd GdHGMK ai gPg GdOQGSI (B((3GdQbGHI GdbVGFjI Ydi GdJMcje hab CMcGe fXGe GdJMcje GdSYhOi(B) . (3ShGA bHd HOA ELQGAGJ GdJMcje ef NdGd GYJeGO hKjbI GdJMcje (B, (3Ch CKfGA SjQ ELQGAGJ GdJMcje (B, (3ChHYO UOhQ Mce GdJMcje (B, (3hEfg HGJ ef GdeSde Hg Cf fXGe GdJMcje djS HeYRd Yf GdbVGA (B, (3hCf dbVGA GdOhdI OhQG eSGYOG heYGhfG ddJMcje NdGa OhQg GdQbGHi h GdGfTGFi(B. (3hbO YGdL GdHGMK ai gPg GdOQGSI GdYOjO ef GdehVhYGJ GdJi HOGgG HHGH JegjOi ceONd Edi GdJMcje (B, (3Ke bSe GdHMK Edi KdGKI CHhGH JfGhd ai GdHGH GdChd JMJ YfhGf GdQbGHI GdbVGFjI GdSGHbI Ydi HOA ELQGAGJ GdJMcje (B, (3ef NdGd aUdjf geG GYJeGO hKjbI GdJMcje (B,(3hJTcjd gjFI GdJMcje (B, (3CeG GdHGH GdKGfi HYfhGf GdQbGHI GdbVGFjI HYO HOA ELQGAGJ GdJMcje abO JYQV GdHGMK dgG ai KdGKI aUhd Ydi GdJhGdi (B, (3QO GdeMce (B,(3YOe UOhQ Mce GdJMcje NdGd GdeOI GdeMOOI (B, (3GdMUhd Ydi COdI GdGKHGJ h GJNGP GdJOGHjQ GdhbJjI hGdJMaXjI ai eLGd GdJMcje (B,(3GeG GdHGH GdKGdK (B: (3aNUUI GdHGMK ddQbGjI GdbVGFjI GddGMbI Ydi UOhQ Mce GdJMcje h Pdc ai aUdjf GdChd Mce GdJMcje (B, (3h GdKGfi JfajP Mce GdJMcje(B. (3hbO GdHGMK GdYOjO ef GdfJGFL h GdJhUjGJ CHQRgG (B, (3EUOGQ fXGe JMcje MOjK HGdGSJQTGO HGdbGfhf GdfehPLi ddJMcje GdUGOQ ef dLfI GdCee GdeJMOI ddbGfhf GdJLGQi (B1985 ((3GdCfSJQGd(B).s
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2010.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B301-318.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJMcjes; (3GdQbGHI GdbVGFjIs; (3GYJeGO hKjbg GdJMcjes; (3ELQGAGJ GdJMcjes; (3Mce GdJMcjes; (3gjFg GdJMcjes; (3Mce GdJMcje s; (3GdJOGHjQ GdhbJjIs; (3GdJOGHjQ GdJMaXjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs